Implementation of environmental accounting to waste management operational costs of PKU Muhammadiyah Gamping hospital - Eni Wulandari; Muhamad Rifandi (Proceeding International Conference on Accounting and Finance, 2023)
This research is a qualitative descriptive study conducted at the PKU Muhammadiyah Gamping Hospital. This study aims to overview the application of environmental accounting at PKU Muhammadiyah Gamping Hospital and to find out whether the financial reports at PKU Muhammadiyah Gamping Hospital are following the application of PSAK No.1. This study indicates that the PKU Muhammadiyah Gamping Hospital has implemented environmental accounting, which is quite perfect in undergoing these stages. Since there are already some elements related to waste management costs that have separate accounts, it is just that the recording in the financial statements has not been made separately, as in the environmental cost report recording by Hansen and Mowen (2009). PKU Muhammadiyah Gamping Hospital is quite perfect in implementing environmental accounting, although there is no specific report on environmental cost and conservation benefits. Furthermore, for the financial report presentation, PKU Muhammadiyah Gamping Hospital has not fully implemented PSAK No. 1. Nevertheless, in compile financial reports, PKU Muhammadiyah Gamping hospital has used PSAK in general as the guideline for compiling financial reports.